Pelatihan Penggunaan Jangka Sorong Siswa Madrasah Aliyah Singosari - Agus Harijono; Nanang Qosim; Gumono Gumono; AM MUFARRIH (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Science learning is related to experimental and observational activities. Learning media is needed in the preliminary phase to increase students' motivation in studying science learning. The caliper is a physics measuring instrument that is widely used in the classroom. Measuring instrument is an instrument used to compare measurement parameters with a predetermined standard. Things that need to be considered in the use of measuring instruments include specifications, types and functions of measuring instruments. The use of dimensional measuring tools such as a caliper has a function to measure the length, thickness, length, inner diameter, outer diameter and depth of the workpiece. Each measuring instrument has a different accuracy and precision. MA Almaarif Singosari is one of the private schools in Malang Regency. This school has a science laboratory for practicum for its students, but the existing equipment is not sufficient to meet the number of students, so the practical experience of the students is still lacking. One of the tools needed is a caliper measuring tool. The purpose of this PKM activity is to increase students' knowledge about measurement techniques using a caliper in theory and practice directly on the learning media that has been provided. The caliper used in this PKM activity has a precision of 0.1 mm and 0.05 mm. The measurement test object is a cylindrical workpiece with dimensions that represent various types of measurements using a caliper. The stages of this PKM activity include field surveys, making measurement objects, procurement of caliper and training on the use of caliper. The results of this training activity proved to be able to increase students' knowledge and skills in using caliper quickly and accurately. So that it can support students' abilities while working or continuing to study. In addition, the school also received additional facilities in the form of calipers and measurement aids so that they could improve the quality of science learning at MA Almaarif Singosari.